2022
DOI: 10.1101/2022.02.08.22270506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symptoms and severity in vaccinated and unvaccinated patients hospitalised with SARS-CoV-2 delta (B.1.617.2) variant infection

Abstract: Background: The diffusion of the SARS-CoV-2 delta (B.1.617.2) variant and the waning of immune response after primary Covid-19 vaccination favoured the breakthrough SARS-CoV-2 infections in vaccinated subjects. To assess the impact of vaccination, we determined the severity of infection in hospitalised patients according to vaccine status. Methods: We retrospectively analysed data from patients hospitalised in 10 centres with a SARS-CoV-2 infection (delta variant) from July to November 2021: i) all patients wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A recent study evaluating the possible reasons for the mortality following COVID-19 vaccination found that the deaths are due to pre-existing comorbidities and not due to the vaccination or the failure of vaccines to extend the protection [ 87 ]. A retrospectively analysed report showed that among patients hospitalised with a SARS-CoV-2 delta variant (B.1.617.2) infection, vaccination was associated with less severity, even in the presence of comorbidities [ 88 ]. In the present study, we observed that the recovery and death rate in vaccinated patients with comorbidities was better than the unvaccinated patients with comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluating the possible reasons for the mortality following COVID-19 vaccination found that the deaths are due to pre-existing comorbidities and not due to the vaccination or the failure of vaccines to extend the protection [ 87 ]. A retrospectively analysed report showed that among patients hospitalised with a SARS-CoV-2 delta variant (B.1.617.2) infection, vaccination was associated with less severity, even in the presence of comorbidities [ 88 ]. In the present study, we observed that the recovery and death rate in vaccinated patients with comorbidities was better than the unvaccinated patients with comorbidities.…”
Section: Discussionmentioning
confidence: 99%